Divercities understanding super diversity in deprived and mixed neigbourhoods - Oosterlynck, Stijn ca. 20./21. Jh; Verschraegen, Gert 1973-; Kempen, Ronald van (Policy Press, 2019)
This edited collection provides a comparative international perspective on superdiversity in cities, with explicit attention given to social inequality and social exclusion on a neighbourhood level. Focusing on the active and creative ways in which residents come together, the book uncovers the ways in which national and local contexts shape living in diversity
Keywords: Stadtviertel; Vielfalt; Stadt; Multikulturelle Gesellschaft; Diversité culturelle; Sociologie urbaine; Cultural pluralism; Sociology, Urban; Aufsatzsammlung